The influence of acidity of the film-forming solution on the structure and properties of thin SnO2 films - Dmitriyeva, E.A.; Grushevskaya, E.A.; Mukhamedshina, D.M.; Mit, K.A.; Lebedev, I.A. (Recent Contributions to Physics, 2020)
The paper considers the effect of acidity of film-forming solutions on the structure and optical properties of thin SnO2 films obtained by sol-gel method. For studying this, a series of solutions with a concentration of tin ions of 0.12 mol/l was prepared with the addition of a different amount of concentrated aqueous ammonia solution. An aqueous ammonia solution was used to regulate the pH level in the SnCl4/C2H5OH system. Solutions were applied to the substrate by a modified dipping method. The film was applied to one side of the substrate. The samples were dried in air for at least 30 minutes, then annealed in a muffle furnace at 400°C for 15 minutes. The structure of the films was studied using an optical microscope MPE-11. Transmission spectra were measured on a two-beam spectrophotometer SF-256 UVI (wavelength range 190-1200 nm.). During the experiment, a direct dependence of the formation of structures on the surface of the obtained films on the acidity of the initial solutions was revealed. With increasing pH, the growth of structures and a change in their shape were observed. The obtained results extend the fundamental knowledge in the field of development of methods for controlling the structure of thin SnO2 films, which is an important element in the creation of materials with improved functional properties.